System Performance Test Of Kratom Leaf Crushing Machine - Fransiskus Tobi; Sholahuddin Sholahuddin; Suko Priyono (Universitas Tanjungpura, 2022)
Various activities in processing kratom leaves in the Kapuas Hulu area are carried out manually and using simple tools. This process has a low capacity and can interfere with the workers' health due to exposure to dust from inhaled materials while working. So we need innovation in using machines that can support the work of the community. The purpose of this study was to test the performance of the kratom leaf crusher machine, including production capacity, yield, size distribution of crumbled leaves, electrical power requirements, and effectiveness of bone and leaf separation. This study used an experimental method by testing the performance of the kratom leaf crusher machine. This testing process was carried out 3 times with different sample weights: 2 kg, 3 kg, and 4 kg. Testing the performance of the crumb machine obtained a production capacity of 57,43 kg/hour, leaf yield of 94,4%, electric power of 19,46 watts/kg, a rotational speed of 1501 rpm, and a noise level of 103,2 dB. The distribution of the diameter of the crushed material was more at the size of 0,84 mm. Testing the separator machine obtained a capacity of 7,42 kg/hour, an electric current of 1,9 A, an air speed of 3,9 m/s, and a noise level of 100,6 dB. The effectiveness of separating the clean leaves off the crumb machine was 76,4% lower than the winnowing in the Kapuas Hulu community, which was 81,2%. The study shows that the crumb machine's performance can increase production capacity. However, improvements need to be made, especially in the discharge channel, so there are no gaps and expedite the process of removing materials to reduce material loss during the crumbling process.